The Influence of Make A Match Learning Model on Student Achiement in Class IV SDN Puspajaya Material of Style Benefits in Daily Life - Mira Melinda; M. Fahmi Nugraha; Budi Hendrawan (LPPM Universitas Buana Perjungan Karawang, 2020)
Science learning is the science of natural phenomena in the form of facts generated based on field observations including science. In natural science learning there are several obstacles, namely the low learning achievement of students, in the learning process in the classroom still using conventional learning models only with lectures and centered on textbooks only, there is no group discussion students tend to be passive and the teacher becomes the center of the learning process, so that students in science learning in the classroom feels boring and less challenging so students are less active in class. Based on the problem of difficulties in the learning process, the application of the make a match learning model is expected to be able to improve student achievement in the material benefits of style in everyday life of class IV SDN Puspajaya. The study uses quantitative research methods with experimental research methods using quasi-external design with nonequivalent control group design. The study was conducted at SDN Puspajaya with a population of twenty students by using a saturated sample that divides students into two classes, namely the control class of ten students and the experimental class of ten students. Data collection techniques were performed using pretest and posttest tests and the data were analyzed using SPSS version 23.